Coagulopathy Induced by Veno-Arterial Extracorporeal Membrane Oxygenation Is Associated With a Poor Outcome in Patients With Out-of-Hospital Cardiac Arrest - Tsuchida, Takumi; Wada, Takeshi; Gando, Satoshi (Frontiers in Medicine, 2021)
Background: In recent years, the use of veno-arterial extracorporeal membrane oxygenation (VA-ECMO) in patients with cardiopulmonary arrest who do not respond to conventional resuscitation, has increased. However, despite the development of VA-ECMO, the outcomes of resuscitated patients remain poor. The poor prognosis may be attributed to deterioration owing to the post-cardiac arrest syndrome (PCAS); this includes the systemic inflammatory response and coagulation activation caused by the extracorporeal circulation (VA-ECMO circuit) itself. This study aimed to evaluate the coagulofibrinolytic changes caused by VA-ECMO and to identify predictive factors of poor prognosis. Methods: We analyzed 151 cases of PCAS with witnessed cardiac arrest. As biomarkers, platelet counts, prothrombin time ratio, fibrin/fibrinogen degradation products, fibrinogen, antithrombin, and lactate were recorded from blood samples from the time of delivery to the third day of hospitalization. The maximum (max) and minimum (min) values of each factor during the study period were calculated. To evaluate the impact of VA-ECMO on patients with PCAS, we performed propensity score matching between the patients who received and did not receive VA-ECMO. Sub-analysis was performed for the group with VA-ECMO. Results: There were significant differences in all baseline characteristics and demographics except the time from detection to hospital arrival, percentage of cardiopulmonary resuscitations (CPR) by witnesses, and the initial rhythm between the groups. Propensity score matching adjusted for prehospital factors demonstrated that the patients who received VA-ECMO developed significantly severe coagulation disorders. In a sub-analysis, significant differences were noted in the prothrombin time ratio min, fibrinogen max, antithrombin max, and lactate min between survivors and non-survivors. In particular, the prothrombin time ratio min and antithrombin max were strongly correlated with poor outcome. Conclusion: In the present study, significant coagulopathy was observed in patients who received VA-ECMO for CPR. In particular, in patients receiving VA-ECMO, the minimum prothrombin time ratio and maximum antithrombin by day 3 of hospitalization were strongly correlated with poor outcomes. These results suggest that VA-ECMO-induced coagulopathy can be a promising therapeutic target for patients resuscitated by VA-ECMO.